The effect of sequence specific DNA methylation on restriction endonuclease cleavage. - McClelland, M (1981)
Sequence specific DNA methylation sometimes results in the protection of some or all of a restriction endonucleases' cleavage sites. This is usually, but not always, the result of methylation of one or both strands of DNA at the site characteristic of the corresponding "cognate" modification methylase. The known effects of sequence specific methylation on restriction endonucleases are compiled.